(untitled) (Acta Entomológica Chilena, 2022)
The structure and ultrastructure of C. bistrigata Butler eggs are described. The samples studied were collected in Concepción area. Eggs show eight micropiles and a proportion of 1: 1,4 between primary and secondaiy surface cells. The egg’s color is closed to the egg of Adetomeris microphthalma (Philippi). The absence of ridges and ornamentation is shared with eggs of other known species, like O. socialis and P. cinerascens (Benitez-Mora & Olivares (in press)).